1999
DOI: 10.1152/ajprenal.1999.277.2.f277
|View full text |Cite
|
Sign up to set email alerts
|

Hensin, the polarity reversal protein, is encoded by DMBT1, a gene frequently deleted in malignant gliomas

Abstract: The band 3 anion exchanger is located in the apical membrane of a β-intercalated clonal cell line, whereas the vacuolar H+-ATPase is present in the basolateral membrane. When these cells were seeded at confluent density, they converted to an α-phenotype, localizing each of these proteins to the opposite cell membrane domain. The reversal of polarity is induced by hensin, a 230-kDa extracellular matrix protein. Rabbit kidney hensin is a multidomain protein composed of eight SRCR (“scavenger receptor, cysteine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 28 publications
3
61
0
Order By: Relevance
“…The DMBT1 gene encodes orthologs in rabbit (hensin (Takito et al 1999)), mouse (CRP-ductin (Cheng et al 1996, Madsen et al 2003 and vomeroglandin (Matsushita et al 2000)), rat (ebnerin (Li & Snyder 1995)), bovine (bovine gallbladder mucin (Nunes et al 1995, Mollenhauer et al 2001), human (gp-340 in lung (Holmskov et al 1997 and salivary agglutinin in saliva (Prakobphol et al 2000, Ligtenberg et al 2001), and porcine (sperm binding glycoprotein (SBG; Teijeiro et al 2012)) species. The pig SBG has been shown to be present in the oviduct, at the apical surface of isthmic and ampullar epithelial cells (Perez et al 2006), to bind to the heads of pig sperm (Marini & Cabada 2003) and to be involved in sperm selection in the oviduct (Teijeiro et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The DMBT1 gene encodes orthologs in rabbit (hensin (Takito et al 1999)), mouse (CRP-ductin (Cheng et al 1996, Madsen et al 2003 and vomeroglandin (Matsushita et al 2000)), rat (ebnerin (Li & Snyder 1995)), bovine (bovine gallbladder mucin (Nunes et al 1995, Mollenhauer et al 2001), human (gp-340 in lung (Holmskov et al 1997 and salivary agglutinin in saliva (Prakobphol et al 2000, Ligtenberg et al 2001), and porcine (sperm binding glycoprotein (SBG; Teijeiro et al 2012)) species. The pig SBG has been shown to be present in the oviduct, at the apical surface of isthmic and ampullar epithelial cells (Perez et al 2006), to bind to the heads of pig sperm (Marini & Cabada 2003) and to be involved in sperm selection in the oviduct (Teijeiro et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Each group of investigators has given the gene/protein different names, and there are many proposed functions. The different names include Muclin (12), gp340 (31), salivary agglutinin (16,42), crp-ductin (6), ebnerin (29), hensin (54), vomeroglandin (33), and DMBT1 (37). We coined the name Muclin (mucin-like glycoprotein), which is based on the glycoprotein's biochemical characteristics (8).…”
mentioning
confidence: 99%
“…When a clonal cell line was seeded at low density on a hensincontaining ECM, they developed apical endocytosis and apical microvilli, demonstrating again that the density of seeding was not actually a "contact inhibition" type of phenomenon. 24,25 Apical microvilli require the presence of elaborate cytoskeleton, and indeed we found that high-density cells induce the production of villin and cytokeratin 19, proteins that are absent in low-density cells. All of these phenomena were induced by hensin purified to homogeneity.…”
Section: Conversion Of ␤ To ␣ Cells Is a Form Of Terminal Differentiamentioning
confidence: 57%